Pendampingan Pengembangan Prosedur Pengadaan Persediaan Pada Hotel Salak The Heritage - Widianti, Rosa; Pardede, Robert Pius; Listari, Sinta (Jurnal Abdimas Dedikasi Kesatuan, 2025)
Inventory is a number of goods owned and stored by the company to be sold or used in the production process and resold or used in providing services. Inventory is an important factor in supporting the smooth operation of the company's operations. Therefore, the company must have inventory in order to carry out operational activities and provide good service. So, in order to make inventory available, it is necessary to carry out the inventory procurement process in accordance with established standard procedures. The purpose of this review is to review and find out how the inventory procurement procedure, constraints and efforts to handle obstacles that occur during the inventory procurement process. The review carried out by the authors was at Hotel Salak The Heritage which is located on Ir. H. Juanda street number 8 16121 Bogor. Hotel Salak The Heritage is a company engaged in the service sector. The results of the evaluation in the review that the authors carried out showed that the inventory procurement procedure at Hotel Salak The Heritage was quite good and had been implemented by the parts involved in the procurement process. And there are still obstacles that occur during the procurement process. So the company must have efforts made to handle and minimize the obstacles that occur. Keywords: inventory, procedure, procurement